Multidisciplinary approach as a model for detection and monitoring of psichiatric morbidity in patients treated with interferon and ribavirin - M. Cabré Serres; N. Rudi Sola; C. Pontes García; M. Vergara Gómez; I. Parra Uribe; M. Q. Gorgas Torner (Farmacia Hospitalaria)
Purpose: We aimed to describe the incidence of psychiatric disorders in acohort of HCV infected patients treated with interferon and ribavirin, andtheir impact on treatment adherence and viral response rate (SVR). Materials and methods: Retrospective analysis of a cohort of HCV patientsvisited at an outpatient pharmacy service (OPS). We included all adultpatients monoinfected with HCV who had initiated treatment in 2010. Monitoringof psychiatric disorders was assessed at weeks 0, 4, 12, 24, 48, and72 through the self-administered questionnaires Hospital Anxiety andDepression Scale (HADS) and General Health Questionnaire (Goldberg).Adherence to treatment was assessed by counting of drug dispensations andpatient reporting and drug exposure with the 80/80/80 rule. Virologicresponse was determined by the physician according to standard definitions. Results: Among 76 included patients, 19 (25%) had a preexisting psychiatricdisorder. The incidence of confirmed psychiatric disorders was 33% (n=25),with a peak of abnormal results in the tests by week 12. Overall, 43% ofpatients achieved an SVR. There were not significant differences between strictadherence and SVR in patients with or without medically confirmed disorders(96.0% vs 96,8%; p = NS) and SVR (39% vs 52%; p = NS], respectively. Conclusions: Psychiatric side effects had no effect on adherence to treatmentnor on attainment of SVR. Multidisciplinary monitoring provided duringthe treatment of hepatitis C can contribute to early detection and managementof psychiatric disorders and to improve integrated patient care.